Unusual Polar Filament Structure in Two Microsporidia from Water Reservoirs with Radionuclide and Organic Pollution - M. A. Ovcharenko; D. P. Molloy; Wita, I. (Bulletin of the Polish Academy of Sciences Biology, 1998)
Two species of microsporidia with the unusual polar filament structure were found in Cricotopus silvestris and Microtendipes pedellus larvae which were collected near the zone of influence of the Chernobyl atomic power station (Ukraine) and from a high polluted pond in the Mazurian region of Poland. The first microsporidium had separate unikaryotic spores and was assigned to the family Unikaryonidae Sprague. The diameter of the middle coil of the triple-coiled polar filament of this microsporidium was larger than its two other coils. The observed polar filament was thus neither of isofilar nor of the classical anisofilar type. The second polysporoblastic microsporidium has unikaryotic spores and an uncoiled polar filament and was placed in the family Thelohaniidae Hazard and Oldacre. The rare single macrospores of this microsporidium have a double set of the polar filament complex. The relationship between ultrastructural features of microsporidian spores and water pollution is discussed.
Keywords: biology